Potential of Local Jackfruit of Palu as a Source of Quality Seeds - Enny Adelina, Yohanis Tambing, Mahfudz, Tati Budiarti, Endang Murniati, Lita Sutopo, Bambang Guritno, Kuswanto, Vanny M A Tiwow, Adrianton (International Journal of Advanced Science and Technology, 2020)
Central Sulawesi is well-known for its plants' biodiversity, including the type of jackfruit in Palu, which have an agroecological, strategic geographical location and potential accessibility. The purpose of this study was to identify and characterize the potential of Palu’s jackfruit through its morphology, anatomy, iso-enzymes, resistance to drought stress, compatibility as rootstock, and vigor of storability. The research method using purposive sampling on 50 jackfruit trees. Identification using passport IPGRI data and analyzed using cluster analysis Systat 8.0. Selected accessions were tested for drought stress using free proline analysis, which was obtained two accessions of drought-resistant jackfruit, namely Tulo-5 and Beka-3. Those two types then tested for rootstock compatibility using a split-plot design with two factors. The testing of vigor seed after storage was conducted by using a completely randomized design method of two factorial patterns. Data analysis used variance analysis, and the treatment which gave significant effect was continued with 5% BNJ test. Identification of morphological and anatomical diversity obtained six large groups of different characters of jackfruit in a scale of 2.5 cluster analysis. There are two of jackfruit plants that are resistant to drought, namely jackfruit Tulo-5 and Beka-3 cultivars. After testing the compatibility of the rootstock, Tulo-5 and Beka-3 showed good compatibility with the jackfruit species of Palupi variety. The vigor of storing, the accession of Tulo-5 stored for 5 weeks in the PEG-6000 40% medium capable of maintaining total viability up to 82% while accessing Beka-3 only 3 weeks on the same medium.